Investigating Students' Anxiety on the Use of Grammar in Vocational High Schools - Ananda, Citra Putri; Rufitriansyah, Herlina; Zulfah, Sabilla Aprilia; Apoko, Tri Wintolo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to discover how students experienced their learning anxiety in using English grammar in vocational high schools. This study used a descriptive quantitative method with 36 vocational high students of the eleventh grade in the areas of West Java and Jakarta as the participants in which the data include the participants' perspectives on their learning anxiety of grammar use in English learning. Based on the results, as many as 15% of students experienced a lack of motivation, 49% experienced insecurity, and 37% of students did not understand English grammar. As a result, students experienced significant learning anxiety while using the English language in a discourse without having a strong command of the language. It is then recommended that this study enable vocational high school students and teachers to find solutions to anxiety about using English in order that students can learn English grammar without anxiety or having fears. Keywords: Anxiety; English Learning; Grammar Use; Vocational High School